Beat sugar addiction now! for kids : the cutting-edge program that gets kids off sugar safely, easily, and without fights and drama - Teitelbaum, Jacob (Fair Winds Press, 2012)
"The modern American child's diet is awash in sugar--including mainstays such as juice, chocolate milk, sugary cereals, soda, energy drinks, and fast-food burgers and nuggets with added corn syrup and sweeteners, let alone candy and cookies prevalent at school parties and play dates. Beat Sugar Addiction Now! for Kids gives parents a proven 5-step plan for getting and keeping their child off sugar. Bestselling author and noted physician Dr. Jacob Teitelbaum and pediatric nutrition specialist Deborah Kennedy, Ph.D., give parents a toolkit for avoiding the common pitfalls such as guilt and temper tantrums, managing the 5-step process successfully on a day-to-day basis, and getting their child emotionally, as well as physically, unhooked from sugary drinks, breakfast foods, snacks, and desserts, as well as "hidden" sugars in foods"--